PERANAN KETAHANMALANGAN DAN KREATIVITAS DALAM PEMBELAJARAN MATEMATIKA - Huri Suhendri; Rita Ningsih (JPPM (Jurnal Penelitian dan Pembelajaran Matematika), 2018)
AbtractThis study aims to analyze and prove the existence of influence ketahanmalangan and creativity to the ability of problem solving math. The research method used is survey method with correlational analysis. Population in this research is all students of class X SMK Kharismawita 2, South Jakarta. While the sample of 30 students class X SMK Kharismawita 2, South Jakarta registered in the academic year 2017/2018. The instruments used in this research data collection consisted of: a questionnaire about resilience and creativity, and a written test of mathematics subjects. Test data analysis requirements consist of: normality test, linearity test, and multicollinearity test. The result of three data analysis requirement test obtained by conclusion that the three groups of data come from normal distributed population, the two regression models formed are linear pattern, and there is no relation between the independent variables. Hypothesis testing is done by correlation test and regression test. Results of hypothesis testing and analysis, it concluded that there is influence ketahanmalangan and creativity to the problem solving ability of mathematics. This means that variable ketahanmalangan and creativity play a role in learning mathematics, which affects the variable problem solving skills of mathematics. So in the learning, educators are concerned about the factors ketahanmalangan and creativity of learners and make efforts to improve both these factors through interesting math learning. Keywords: Adversity Quotient, Creativity, Learning Mathematics